Factors influencing green product purchase of adiwiyata and non-adiwiyata high school students in south jakarta - Dunya, Cholifah; Rosyidatun, Eny Supriyati; Solihin, Solihin (JPBIO (Jurnal Pendidikan Biologi), 2025)
The global environmental crisis, exacerbated by unsustainable consumption and escalating plastic waste, underscores the urgency of promoting green product purchasing practices. This study investigates the influence of green product knowledge (GPK), green awareness (GA), and green lifestyle (GL) on green product purchasing practices (PPGP) among Adiwiyata and non-Adiwiyata high school students in South Jakarta. Employing a quantitative approach with a survey method, data were collected from 204 students using a combination of essay-based and Likert-scale questionnaires. Multiple linear regression analysis revealed that GPK, GA, and GL jointly had a significant influence on PPGP, explaining 56.07% of the variance for Adiwiyata students and 36.21% for their non-Adiwiyata counterparts. Partially, only GA and GL significantly affected PPGP among Adiwiyata students, whereas only GL was significant for non-Adiwiyata students. GL emerged as the strongest predictor in both groups, with regression coefficients of 0.6436 and 0.5823, respectively. These findings highlight the importance of embedding behavioral components into environmental education by prioritizing green lifestyle development to foster sustainable consumer behavior among high school students.